Penerimaan Sistem Aplikasi Pegadaian Syariah Digital dalam Proses Transaksi Nasabah - Munawarah, Cut; Rusdi, Rusdi (Regress: Journal of Economics & Management, 2022)
This article aims to discuss the acceptance of digital Islamic pawnshop application systems in customer transaction processes. The use of digital applications in pawnshop services is a new thing in the application of information technology. Pegadaian as a non-banking financial institution is also required to improve in order to be able to keep abreast of developments in digital technology in the financial sector. Sharia principles are applied in the pawnshop system by applying the rahn principle in the pawn contract. Respondents in this study amounted to 112 people who were taken by the convenience sampling method. As many as 74.77% of research respondents said they had heard of the Digital Sharia Pawnshop Application and as many as 61.26% said they had used it. The results of the study show that apart from the compatibility and self-efficacy aspects, all research variables influence the desire of pawnshop customers to use the Digital Sharia Pawnshop Application.